(untitled) (Bangladesh Journal of Pharmacology, 2022)
The protective effect of medroxyprogesterone acetate on propionic acid-induced autism in rats was evaluated. For this purpose, 30 rats were divided into three groups. The significant difference in the levels of IL-17 (p<0.05), IL-2 (p<0.05), and TNF-α (p<0.05), lactate (p<0.05), and nerve growth factor (p<0.05) were found in the medroxyprogesterone-treated group by biochemical analysis. In histopathological examination, the medroxyprogesterone-treated group revealed significant improvement in neural body degeneration, neural count, and dysmorphological changes in both CA1 and CA3 regions. Immunohistochemical examination revealed improvement in glial activity with glial fibrillar acidic protein and morphological changes in Purkinje cells. Magnetic resonance spectroscopy showed an improvement in the level of lactate duplets in the medroxyprogesterone-treated group. To our knowledge, this is the first study, to evaluate the protective effect of medroxyprogesterone on propionic acid-induced autism in rats.